Influence Of Organizational Culture, Work Discipline, And Work Environment On Employee Performance - Bagas Pradana Aulia; Imam Sucipto; Ahmad Gunawan (STIE Binaniaga, 2021)
The purpose of this study is to ascertain the effect of organizational culture, work discipline, and work environment on employee performance at PT Mitsubishi Logistics Indonesia's repack division. The population is comprised of employees of PT Mitsubishi Logistics Indonesia, and the sample size was 74. The sampling technique used in this study is Non-Probability Sampling with a saturated sampling type. Multiple linear regression analysis is used to analyze data using the SPSS software version 25.According to the study's results, corporate culture, work discipline, and work environment positively and substantially influence employee performance concurrently. Then, organizational culture influences employee performance, followed by work discipline and the work environment.